2007
DOI: 10.1002/er.1335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy storage medium (black granite gravel) on the performance of a solar still

Abstract: SUMMARYIn this study, a detailed experiment has been conducted on a single-basin solar still which is modified with energy storage medium of black granite gravel. An attempt has been made to utilize the maximum amount of solar energy and to reduce the heat loss from the sides and bottom of the still. The conventional still is modified with an energy storage medium of black granite gravel of 6 mm size which is provided in the basin for different (quantity) depths. The black granite gravel functions as energy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The additional surfaces resulted in an increased evaporation rate by 53 % in comparison to the conventional single slope solar still. Sakthivel and Shanmugasundaram (2008) studied the effect of different quantity but of the same size (6 mm) black granite gravel as an energy storage medium on the performance (Suneesh et al 2014) of single basin solar still. System showed higher performance with large depth of storage medium.…”
Section: Effect Of Internal and External Reflectorsmentioning
confidence: 99%
“…The additional surfaces resulted in an increased evaporation rate by 53 % in comparison to the conventional single slope solar still. Sakthivel and Shanmugasundaram (2008) studied the effect of different quantity but of the same size (6 mm) black granite gravel as an energy storage medium on the performance (Suneesh et al 2014) of single basin solar still. System showed higher performance with large depth of storage medium.…”
Section: Effect Of Internal and External Reflectorsmentioning
confidence: 99%
“…The results showed that the double basin yields more distillate only when the water depth was maintained at just 1 cm [151]. This is inconsistent, however, with the results of Manivel et al [53] and Sakthivel et al [56] who achieved higher yield with 2.5 or 3 cm water depth. Hitesh (2013) conducted the experiment in a double-basin solar still with a vacuum tube ( fig 46) and black gravel granite attached to it.…”
Section: Elango Et Al (2015)mentioning
confidence: 85%
“…El-Sebaii et al [25] were used aluminu m, copper, stainless steel and mica plates as suspended absorbers material in single basin solar still during experiment.It was found that using metallic plates as suspended absorbers (Aluminu m, Copper and Stainless steel) the daily productivity of still about 15-20% higher than that of the conventional still. But it has problems of corrosion to use metallic plates as suspended absorbers.…”
Section: Mica Pl Atementioning
confidence: 99%